Analysis of Proximate Composition and Functional Properties of Selected Edible Leaves: Nutritional and Therapeutic Implication - Pal, A. D.; Zakir, T. M. (Journal of Scientific Research, 2020)
The present study was designed to document the nutritional and functional properties of Ceylon Spinach, Mustard as well as Pumpkin leaves. These samples were selected owing to their economic affordability and utilization within the local population. Proximate analysis revealed a significant percentage of minerals, proteins, carbohydrates and vitamin C in all the leaf extracts. Phytochemical screening displayed Ceylon Spinach, Pumpkin and Mustard leaves to be rich sources of polyphenols (106.6, 76.24 and 89.86 mg/100 g) and alkaloids (12.8 %, 13.2 % and 16.8 %) respectively. Furthermore, these edible leaves could effectively scavenge 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) and hydrogen peroxide (H2O2) free radicals with Mustard leaves showing the greatest efficiency, hence portraying antioxidant properties. Ceylon Spinach leaves depicted the highest reducing power compared to the other samples. Additionally, the edible leaf extracts were shown to possess anti-bacterial abilities with Mustard leaves displaying the strongest inhibition against growth of both Gram positive (ZOI 18.5mm) and negative bacteria (ZOI 25.5mm). Interestingly, the selected samples could also elevate the growth of probiotic Lactobacillus acidophilus in vitro thereby confirming their prebiotic potential. Therefore, inclusion of these edible leaves in the diet may promote good health owing to their nutritional and therapeutic benefits.